Reputation: 161
I'm puzzled by this behavior of mathematica. The two following expressions should return the same result:
Simplify[(1 - w)^2 Sum[w^(k+kp) Sum[If[l == lp, 1, 0], {l, 0, k}, {lp, 0, kp}],
{k,0, \[Infinity]}, {kp, 0, \[Infinity]}]]
returns:
(-1 - w + w^3)/(-1 + w^2)
whereas the strictly equivalent:
Simplify[(1 - w)^2 Sum[w^(k+kp) Min[k, kp],{k,0,\[Infinity]},{kp,0,\[Infinity]}]
+ (1 - w)^2 Sum[w^(k+kp) ,{k,0,\[Infinity]},{kp,0,\[Infinity]}]]
returns:
1/(1 - w^2)
Upvotes: 0
Views: 99
Reputation: 1242
Not an answer, but if you use
$$\sum_{k=0}^{\infty} \sum_{l=0}^{k} = \sum_{l=0}^{\infty} \sum_{k=l}^{\infty}$$
then :
sum1 = Simplify[(1 - w)^2
Sum[w^(k + kp) Sum[KroneckerDelta[l, lp] , {l, 0, k}, {lp, 0, kp}],
{k, 0, Infinity}, {kp, 0, Infinity}]]
(* (-2 + w + w^2 - w^3)/(-1 + w^2) *)
but
sum2 = Simplify[(1 - w)^2
Sum[KroneckerDelta[l, lp]
Sum[w^(k + kp), {k, l, Infinity}, {kp, lp, Infinity}] ,
{l, 0, Infinity}, {lp, 0, Infinity}]]
(* 1/(1 - w^2) *)
Upvotes: 1